Crosscutting concepts and achievement: Is a sense of size and scale related to achievement in science and mathematics?. Issue 3 (10th October 2018) - Chesnutt, Katherine; Gail Jones, M.; Corin, Elysa N.; Hite, Rebecca; Childers, Gina; Perez, Mariana P.; Cayton, Emily; Ennes, Megan
Abstract: This study examined the relationship between students' ( N  = 229) concepts of size and scale and students' achievement in science and mathematics over a 3‐year period. Size and scale are considered one of the big ideas in science that permeates disparate science and mathematics content areas, yet little is known about the relationship between students' conceptualization of size and scale and students' achievement in science and mathematics. The study used a modified panel longitudinal design to follow the same class of students over a 3‐year period. The goal was to explore whether understandings of size and scale are related to achievement in mathematics and science. Results indicated a strong positive significant relationship existed between students' understanding of size and scale and students' science achievement in grades 5 and 8. There was a positive significant relationship between students' concepts of size and scale and students' mathematics achievement in grades 5, 6, 7, and 8. An examination of the relationships is included as well as a discussion of the integration of crosscutting concepts into science and mathematics instruction as a way to support deep learning.